Preface - Varga, Imre; Kovásznai, Gergely (Acta Cybernetica, 2025)
In today's dynamic and ever-evolving digital landscape, applied informatics plays a pivotal role in shaping the future of technology. From refining algorithms for enhanced data analysis to optimizing communication networks and advancing artificial intelligence, the realm of applied informatics continues to drive innovation and transformation across industries. This current Special Issue features contributions from the 12th International Conference on Applied Informatics (ICAI 2023), which was held in Eger, Hungary on March 2-4, 2023. These research papers explore novel insights, innovative methodologies, and practical applications within the field of computer science and informatics. Each of them represents a valuable contribution to the applied informatics field and offers insights that bridge the gap between theory and practical application. They are a testament to the diversity and dynamism of our field, showcasing a wide range of research topics and applications.